2012
DOI: 10.21836/pem20120302
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical characteristics of the equine Autologous Conditioned Plasma® (ACP)

Abstract: ZusammenfassungThrombozytenkonzentrate (TZK) werden gegenwärtig in der Pferdeorthopädie häufig therapeutisch eingesetzt. Bei dieser autologen Therapieform werden Thrombozyten (TZ) in das geschädigte Gewebe appliziert, damit sie ihre heilungsfördernden Wachstumsfaktoren (GF) lokal freisetzen können. Zu den wichtigsten GF für die Gewebsregeneration zählen PDGF-BB (platelet-derived growth factor BB) und TGF-b 1 (transforming growth factor b 1 ). Autologous Conditioned Plasma ® (ACP) stellt eine relativ neue, einf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
16
2
7

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(28 citation statements)
references
References 19 publications
3
16
2
7
Order By: Relevance
“…Nevertheless, as conventional plasma and ACP samples were treated identically, there is no doubt about the highly significant increase in PDGF-BB concentration in ACP samples. Even though there was a significant difference in the PDGF-BB concentration, these results were significantly lower when compared to previously reported values (Hessel et al 2014, Kissich et al 2012. Interestingly, a recent study suggests that ACP is apparently not as efficient concentrating PDGF-BB and TGF-b as it was previously reported (Hessel et al 2014), this might suggest that the growth factor differences found in these 3 studies could have been caused by a low repeatability of the ACP kit when using horse blood.…”
Section: Discussioncontrasting
confidence: 72%
See 3 more Smart Citations
“…Nevertheless, as conventional plasma and ACP samples were treated identically, there is no doubt about the highly significant increase in PDGF-BB concentration in ACP samples. Even though there was a significant difference in the PDGF-BB concentration, these results were significantly lower when compared to previously reported values (Hessel et al 2014, Kissich et al 2012. Interestingly, a recent study suggests that ACP is apparently not as efficient concentrating PDGF-BB and TGF-b as it was previously reported (Hessel et al 2014), this might suggest that the growth factor differences found in these 3 studies could have been caused by a low repeatability of the ACP kit when using horse blood.…”
Section: Discussioncontrasting
confidence: 72%
“…Interestingly, the PDGF-BB concentrations achieved in this study were lower and the TGF-b were higher (but not significantly higher than conventional plasma) than the reported values using anticoagulant citrate dextrose solution A (ACD-A) (Hessel et al 2014, Kissich et al 2012. Several studies have !…”
Section: Discussioncontrasting
confidence: 52%
See 2 more Smart Citations
“…Zusätzlich zieht eine größere Menge an Zellmediatoren nicht unbedingt eine verbesserte Geweberegeneration nach sich, so dass eine Überprüfung dieser Effekte in einer kontrollierten In vivo-Studie erfolgen müsste (Giusti et al 2009). Für die Bestimmung der TGF-b 1 und PDGF-BB-Konzentrationen wurden humanspezifische ELISA-Kits verwendet, für die aber einerseits bereits in vorangegangenen Studien Kreuzreaktio-nen mit Pferdeantikörpern nachgewiesen wurden (Sutter et al 2004, Schnabel et al 2008, Tablin et al 2008) und andererseits von der Arbeitsgruppe der vorliegenden Studie ebenfalls für das Pferd validiert wurden (Kissich et al 2012 …”
Section: Limitierung Dieser Studieunclassified